Analisis Perbandingan Nilai Gizi Ulat Tepung (Tenebrio Molitor) dengan Perlakuan Katalis dan Substrat yang Berbeda - Muh. Satria Arhamza; Mohammad Mirwan (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This research aims to analyze the comparative nutritional value of mealworms (Tenebrio molitor) cultivated using various catalysts and organic substrates in the bioconversion process. The research was carried out through seven treatment groups that combined organic waste with two types of catalyst, namely amino acids and leachate, as well as three types of substrate, namely rice bran, coffee grounds and sawdust. Each treatment was maintained in the same environmental conditions for 30 days. Nutrient parameters including protein, fat, water and ash levels were analyzed using the proximate analysis method based on the AOAC procedure (2016). (Gaithersburg, 2016) Data were processed descriptively to compare differences in nutritional composition between treatments. The results showed that the combination of leachate and rice bran produced the highest protein content (21.35%), while the sawdust-based treatment showed the lowest nutrient content due to limited digestibility. These findings indicate that the type of catalyst and substrate substantially influence the nutritional composition of T. molitor, and optimal bioconversion efficiency can be achieved under conditions of balanced organic substrate and catalyst. The integration of biocatalyst and substrate modification thus improves the nutritional quality of mealworms while supporting sustainable waste management practices.